Community Stories and Growth Through Research-Based Theatre (LEARNing Landscapes, 2018)
Community members and staff at the University of British Columbia (UBC) Learning Exchange collectively created a theatre piece, based on stories from Vancouver’s Downtown Eastside (DTES), entitled Voices UP! This article examines the impact this project had on four DTES community members who took part in the collective creation process. The results are presented as both a thematic analysis and a short play script, entitled Give Me Your Hands. Give Me Your Hands is a play about making a play, illustrating the shared and individual learning experiences of those who took part in a community-based collaborative theatre process.
Keywords: research-based theatre; arts-based learning; collective creation; community arts project